Revealing zooplankton diversity in the midnight zone - González, Carolina E.; Blanco-Bercial, Leocadio; Escribano, Rubén; Fernández-Urruzola, Igor; Rivera, Reinaldo; Ulloa, Osvaldo (Frontiers in Marine Science, 2023)
Zooplankton diversity in the deep “midnight zone” (>1000 m), where sunlight does not reach, remains largely unknown. Uncovering such diversity has been challenging because of the major difficulties in sampling deep pelagic fauna and identifying many (unknown) species that belong to these complex swimmer assemblages. In this study, we evaluated zooplankton diversity using two taxonomic marker genes: mitochondrial cytochrome oxidase subunit 1 (COI) and nuclear 18S ribosomal RNA (18S). We collected samples from plankton net tows, ranging from the surface to a depth of 5000 m above the Atacama Trench in the Southeast Pacific. Our study aimed to assess the zooplankton diversity among layers from the upper 1000 m to the ultra-deep abyssopelagic zone to test the hypothesis of decreasing diversity with depth resulting from limited carbon sources. The results showed unique, highly vertically structured communities within the five depth strata sampled, with maximal species richness observed in the upper bathypelagic layer (1000–2000 m). The high species richness of zooplankton (>750 OTUS) at these depths was higher than that found in the upper 1000 m. The vertical diversity trend exhibited a pattern similar to the well-known vertical pattern described for the benthic system. However, a large part of this diversity was either unknown (>50%) or could not be assigned to any known species in current genetic diversity databases. DNA analysis showed that the Calanoid copepods, mostly represented by Subeucalanus monachus, the Euphausiacea, Euphausia mucronata, and the halocypridade, Paraconchoecia dasyophthalma, dominated the community. Water column temperature, dissolved oxygen, particulate carbon, and nitrogen appeared to be related to the observed vertical diversity pattern. Our findings revealed rich and little-known zooplankton diversity in the deep sea, emphasizing the importance of further exploration of this ecosystem to conserve and protect its unique biota.